Investigation of Passenger Car Using Macpherson Strut for Front Suspension System PT.1: Vehicle Behavior Variation of Time Response - Tanti, Ali; R. A., Bakar; Gan, Leong Ming (2016)
It has been decade researchers has been conducting researches on the topics concerning vehicle behavior. Suspension system, driving maneuver and road profile are the particular parameters in order to achieve the aim in vehicle behavior understanding. This paper combined these three criteria by means of using a passenger car equipped with MacPherson strut front suspension undergoes different driving behavior. For this study, Proton Persona Sedan 1.6 Manual Transmission Base Line was used to investigate MacPherson strut suspension system. Data were collected using DEWESoft Software. This experiment resulted on the vehicle behavior based on the velocity and direction variation of time response. The most simple quarter car model described requires basic dynamic phenomena. It can be concluded that MacPherson strut suspension system has an effect on not only vehicle behavior but also comfort ride. These findings provide the following insights for future research in suspension vibration in order to optimize the performance of MacPherson strut suspension system.